Assessing usability and perceived impact of an infographic module for Ibn Aqil’s grammar in a public Malaysian university context - Abdul-Hamid, Mohd Fauzi; Sahrir, Muhammad Sabri; Yahaya, Mohd Firdaus; Sha'ari, Shaferul Hafes; Hassan, Isyaku; Yusop, Khadijah (ATI, Belgium, 2025)
Traditional Turath textbooks, such as Syarah Ibn Aqil, are core to learning Arabic grammar (Nahu), yet their dense content often poses challenges for students. This study assessed the usability and perceived learning impact of an infographic-based module designed to simplify key concepts from Ibn Aqil’s syntax. A usability survey was administered to 73 students enrolled in a related course at a Malaysian public university. Data collected via questionnaire were analyzed using SPSS to evaluate the module's content, design, usability, and perceived influence. Results indicated high mean scores across all constructs (ranging from 4.64 to 4.73), reflecting strong student acceptance. Participants reported that the infographics enhanced their motivation and helped them focus on essential concepts. The findings suggest that infographic modules are a wellreceived and pedagogically valuable supplement to traditional grammar texts, capable of enriching the learning experience through visual presentation.